Education in the Works of Vićentije Rakić - Parlić Božović, Jasna Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The movement for a "new school and a modern education", whose representative was Vićentije Rakić, included all the civilized countries between the two world wars, and has also emerged in our country at this time. At that time they felt deficiencies and poor educational effect Our schools all over, and the need for its modern contemporary pedagogical reform in the spirit stood out and imposed harder. Increasingly there was a need to adapt to the requirements of our school new time and then developmental and educational needs of our national community, to our new school could be more successful if implemented contemporary folk education and youth to act as hard towards a complete and unique spiritual formation our new national community. This paper will attempt to be presenting one of the representatives of the pedagogical orientation, Vićentijе Rakic ​​through the analysis of concepts education in his works.